Bilateral medial medullary infarction: three cases report and literatures review - FANG Rong; WU Bin; DENG Wei⁃ping; WANG Xiao⁃dan (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective Bilateral medial medullary infarction (MMI) is prone to misdiagnosis. This study summarizes the clinical characteristics of MMI, in order to provide reference to clinicians. Methods and Results The clinical data of the 3 patients with acute bilateral MMI treated in Ruijin Hospital North Campus affiliated to Shanghai Jiaotong University School of Medicine from January 2017 to January 2022 were collected. All 3 patients had acute onset, one case had acute myelitis⁃like manifestations (rapidly progressive quadriplegia), one case had intractable hiccup, and the other one had unilateral limb numbness and fatigue as the first manifestation, accompanied by hypoglossal palsy. The head MRI showed acute bilateral MMI (one case without acute lesions on early MRI). Two cases were misdiagnosed because of either presenting lower motor neuron damage signs or having atypical symptoms. All patients improved after antithrombotic therapy for acute cerebral infarction. Conclusions The clinical manifestations of acute bilateral MMI are diverse, and it's easy to be misdiagnosed in the early stage. The diagnosis is mainly based on clinical manifestations and head MRI, which requires early recognition and timely antithrombotic treatment for acute cerebral infarction. The main distinguishing points are whether there are risk factors for stroke, upper motor neuron damage signs, and the treatment was effective.